The social construction of diversity : recasting the master narrative of industrial nations - Harzig, Christiane; Juteau Lee, Danielle (Berghahn Books, 2003)
Though the composition of the populace of industrial nations has changed dramatically since the 1950s, public discourse and scholarship, however, often remain welded to traditional concepts of national cultures, ignoring the multicultural realities of most of today's western societies. Through detailed studies, this volume shows how the diversity affects the personal lives of individuals, how it shapes and changes private, national and international relations and to what extent institutions and legal systems are confronted with changing demands from a more culturally diverse clientele. Far from being an external factor of society, this volume shows, diversity has become an integral part of people's lives, affecting their personal, institutional, and economic interaction.